The immune checkpoint ligand PD-L1 is upregulated in EMT-activated human breast cancer cells by a mechanism involving ZEB-1 and miR-200. (2nd January 2017) - Noman, Muhammad Zaeem; Janji, Bassam; Abdou, Abderemane; Hasmim, Meriem; Terry, Stéphane; Tan, Tuan Zea; Mami-Chouaib, Fathia; Thiery, Jean Paul; Chouaib, Salem
ABSTRACT: PD-L1 expression and regulation by mesenchymal tumor cells remain largely undefined. Here, we report that among different EMT-activated MCF7 human breast cancer cell clones, PD-L1 was differentially upregulated in MCF7 sh-WISP2, MCF7–1001/2101, and MDA-MB-231 cells but not in MCF7 SNAI1 and MCF7 SNAI1–6SA cells. Mechanistic investigations revealed that siRNA silencing of ZEB-1, but not SNAI1, TWIST, or SLUG and overexpression of miR200 family members in MCF7 sh-WISP2 cells strongly decreased PD-L1 expression. Thus, we propose that PD-L1 expression in EMT-activated breast cancer cells depends on the EMT-TF involved in EMT activation. Interestingly, siRNA-mediated targeting of PD-L1 or antibody-mediated PD-L1 block restored the susceptibility of highly resistant MCF7 sh-WISP2 and MCF7–2101 cells to CTL-mediated killing. Additionally, these results provide a novel preclinical rationale to explore EMT inhibitors as adjuvants to boost immunotherapeutic responses in subgroups of patients in whom malignant progression is driven by different EMT-TFs.